Analisis Proses Pembelajaran Matematika Berbasis Daring Pada Siswa Kelas Tinggi Sekolah Dasar - Firly Cahyani Hermawantie; Astri Sutisnawati; Luthfi Hamdani Maula (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
This study aims to describe the online-based mathematics learning process on online- for upper-class students at SDN Lembursitu. This type of research uses a qualitative descriptive method, and implemented in class IV-B SDN Lembursitu Sukabumi City. Data collection techniques used in this study were interviews in the online-based learning process. The data analysis technique in this study uses data reduction, , data presentation and drawing conclusions. The results of this study indicate that the obstacles that occur are that some students find it difficult in the learning process using online mode , communication tools and the condition of each student who do not have adequate facilities to support the learning process. The effort made by the teacher is by working together between teachers, schools and parents.